Dream I tell you - Cixous, Hélène, 1937- (Frontiers of theory., 2006)
This book is an account of, and commentary on, a collection of dreams by the novelist, playwright and theorist Hélène Cixous. As such the book presents a rich poetic experience and is a key document in understanding Cixous' writing practice. Jacques Derrida's commentary on Dream I Tell You is published in 'The Frontiers of Theory' series as Geneses, Genealogies, Genres and Genius.Key FeaturesImportance of Helene Cixous to contemporary literary and French feminist theory.The poetic, autobiographical quality of the writing.Significance of the book to the Cixous oeuvre.